A Study on the Strategy of Modern Border Governance in the Qing Dynasty -- A Brief Discussion on the Governance Strategy of Zhao Erfeng during his tenure as the Resident Minister in Tibet - Jiang, Yetao (Transactions on Social Science, Education and Humanities Research, 2024)
In the late Qing Dynasty, in order to consolidate the southwest border and resist the invasion of British colonizers. The central administrative group of the Qing Dynasty carried out a series of governance and business activities on the Xichuan border. In this series of activities, Zhao Erfeng, who was then the Minister of Border Affairs of Sichuan and Yunnan, was known as the "Zhao Butcher". He cruelly suppressed the national movement with iron and blood methods, and implemented strategies such as land reform and new policies, which greatly changed the form of border areas in Sichuan. This article aims to explore the development process of modern ethnic relations and border governance by exploring Zhao Erfeng's governance period, extracting the ruling ideas of Qing rulers towards ethnic border areas, and exploring the development process of modern ethnic relations and border governance.